ANALISIS PENINGKATAN KESEJAHTERAAN MUSTAHIK DARI SEGI SPIRITUAL DAN MATERIAL MENGGUNAKAN METODE CIBEST (STUDI KASUS: PROGRAM KUM DI YDSF MALANG) - Naufal Mahadika Driantama; Sri Muljaningsih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Poverty in Indonesia is a complex and structured problem. Therefore, comprehensive policies are needed to address poverty. Empowerment of hive-based, productive-based societies can have a positive and optimal impact on reducing poverty, while also improving the economic well-being. Cibest's methods become one of the alternatives to measure the impossible's spiritual and material well-being. The purpose of this study is to determine poverty conditions before and after receiving help from poor kum DSF program and to see the role of laznas in empowering zakat. The research methods used use a descriptive quantitative analysis approach and use primary data. The source of this research is umkm the beneficiary of the wretched kum YDSF program. In the data collection technique using a likert scale questionnaire. The result of this study was that the first change in living conditions in quadrant ii (poor spiritually) was 7 mustahik, reducing only 2 improbable. It is impossible to move to the prosperous quadrant of spiritual and material prosperity. For the capitals financing financing scheme of empowering the mustahik at the poverty poverty is divided into four elementary, pre intermediate, intermediate, and advanced classes.